Bizarre notosuchian crocodyliform with associated eggs from the upper cretaceous of Bolivia - Novas, Fernando Emilio (2009)
The Mesozoic record of fossil vertebrates from Bolivia (Fig. 1) was restricted heretofore to Campanian–Maastrichtian dinosaur footprints (e.g., Leonardi, 1989; Sua´rez Riglos, 1995; Lockley et al., 2002; McCrea et al., 2001; Meyer et al., 2001) and isolated and poorly informative dinosaur teeth and bones (Aguilera et al., 1989; Gutierrez and Marshall, 1994). Discovery of several, almost complete skeletons of a new notosuchian taxon constitutes the most important body-fossil discovery for the Mesozoic of Bolivia, adding substantially to the meager record of this region of South America. At least two partially disarticulated skeletons and two complete eggs were found together in a small area, constituting one of the few available associations of skeletal remains and eggs for extinct crocodyliforms. In this paper we describe this material as a new genus and species. We consider only the skull morphology, because most of available postcranial remains are still under technical preparation.